Antibiotic resistance and molecular characteristics of methicillin-resistant Staphylococcus epidermidis recovered from hospital personnel in China. (September 2020) - Xu, Zhen; Cave, Rory; Chen, Liqin; Yangkyi, Tsetan; Liu, Yan; Li, Ke; Meng, Ge; Niu, Kaijun; Zhang, Wanqi; Tang, Naijun; Shen, Jun; Mkrtchyan, Hermine V.
Highlights: The colonization rate of MRSE (91%) was unusually high among hospital personnel from two hospitals in Tianjin, China, who were carriers of Staphylococcus epidermidis . The MRSE isolates had high resistance rates towards β-lactam antibiotics, but low resistance rates against non-β-lactam antibiotics. The majority of MRSE in this study belonged to cluster II domain of CC2. ST59-IV was the predominant clone among isolates recovered from hospital personnel, a sequence type that was reportedly associated with clinical infections. New MLST types were determined, thus confirming the genetic diversity of these isolates. The hospital personnel may well act as a reservoir of antimicrobial resistant pathogens. Abstract: Objectives: Staphylococcus epidermidis is a major nosocomial pathogen predominantly associated with indwelling medical device infections. Studies reporting on S. epidermidis recovered from hospital personnel in China are scarce. The aim of this study was to evaluate the carriage and antibiotic resistance of S. epidermidis among the hospital personnel in Tianjin, China and provide insights into their genetic diversity. Methods: One hundred and seven S. epidermidis isolates were recovered from 68 hospital personnel in two public hospitals in Tianjin between March 2018 and May 2018. Staphylococcal cassette chromosome mec (SCC mec ) types were determined by the combination of mec and ccr complexes. Multi-locus sequence typing was used to determine the sequence types (ST) of S. epidermidis isolates. Results: Sixty-two (76.5%) isolates were determined to be methicillin-resistant S. epidermidis (MRSE). Thirty-five (51%) of 68 hospital personnel carried S. epidermidis, of which 32 (91%) were carriers of MRSE. All 62 MRSE isolates had high levels of resistance to penicillin (90%) and cefoxitin (100%). Thirty-seven (60%) isolates carried SCC mec type IV, followed by 15 (24%) carrying SCC mec V, and 4 (6%) SCC mec II. Novel STs were assigned to four S. epidermidis isolates (ST832, ST833, ST834 and ST835). Conclusions: In this study, the majority of MRSE belonged to cluster II domain of CC2. The ST59-IV was a dominant clone among isolates recovered from hospital personnel. Determination of new MLST types confirmed the genetic diversity of these isolates. These observations highlight the need to review the infection control strategies to reduce the carriage of MRSE among hospital personnel.